Manajemen Jaringan dalam Perspektif Strukturasi - Pratikno Pratikno (Magister Ilmu Administrasi Publik, 2008)
Horizontal relations in the governance model are inadequately managed by intra-organizational approach. To dealt with these horizontal relations, however, the juricidial and hierarchical instruments of intra-organization have apparaently lost its relevance and even problematic. Conversely, these relations need for the more soft and informal instruments in achieving consensus and synergy among relatively autonomous actors. in consequence, the network-based organization theories shall be immediately developed.The most important task in developing these theories lain on how to formulate a set of technical manners in ordet to establish ann institutionalized and sustainable energy. This paper attempts to initially develop a network theory and network governance instrumentation in the context of anarchical (non-autoritative) relations. By adopting the seminal concept of structure-agency duality in the Giddens; structuration theory, network management could be strategically defined as a social action of the agency (game management) to (re)constitute the constraining potentials in order to facilitate and enable the processes of synergy-building.